TIPOLOGI PANTAI UNTUK OLAHRAGA SURFING DI PULAU KARAM KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Ardian Syahroni; Helfia Edial; widya Prarikeslan (JURUSAN GEOGRAFI FIS UNP, 2017)
This study is purposed to: 1) find out shore typology in Karam Island Koto XI Tarusan district Pesisir Selatan regency, 2) to find out wave characteristics (length & slam index), 3) to find out wave types for surfing activity in Karam Island Koto XI Tarusan district Pesisir Selatan regency.This study was classified into descriptive study with survey method. Data in this study was primary data that came from field observation and secondary data which was collected from related agencies. Mapping unit that used in this study was shore line with study object was shore in Karam Island Koto XI Tarusan district Pesisir Selatan regency. Sample was obtained by purposive sampling technique. Study findings are: 1) shore topology is bura (alluvial coast) and marine coast, 2) average wave length (L0) and average slam height (Hb) are 177.58 m and 1.73 m, respectively, 3) wave types are plunging, spilling, and surging. Shore typology and wave type based on wave height and wave period in area of sample I in Karam Island Koto XI Tarusan district Pesisir Selatan regency is suitable for amateur surfer.